Return to Play after Anterior Cruciate Ligament Reconstruction among Amateur Soccer Players - Alonso, Julián; Malig, Samuel; Fontboté, Cristián; Azar, Camilo; Vergara, Francisco; Yáñez, Roberto (Revista Chilena de Ortopedia y Traumatología, 2019)
Objective The aim of the present study is to assess the return to play among amateur soccer league players after anterior cruciate ligament (ACL) reconstruction.Materials and Method The surgical protocols of ACL reconstruction surgeries performed in a sports medicine clinic from July 1st, 2013, to June 30th, 2014, were included in the study. Only the charts of amateur soccer league players who played once or twice a week were selected. The follow-up time was calculated as the number of months between surgery and the telephone survey. At the follow-up, the current status of the soccer playing was recorded. Those patients who were no longer playing in a team were asked what kind of sport they were currently practicing, as well as the main reason for not returning to team playing.Results A total of 61 (25.6%) patients met the inclusion criteria. The mean follow-up time was of 22.4 ± 3.4 months. At the follow-up, 30 (49.1%) patients were playing in amateur soccer teams. Among the patients who were no longer playing in a team, 19 (61.2%) were playing soccer occasionally, 11 (35.4%) were practicing other sports, and 1 developed a sedentary life style. The reasons for not returning to team playing were: fear of reinjury in 26%; knee symptoms in 26%; lack of confidence in the knee in 23%, family or job commitments in 23%; and not being eligible to participate in competitive sports in 2%.Conclusion After an average of two years of ACL reconstruction, only half of the amateur soccer league players return to play.
Keywords: anterior ligament cruciate reconstruction; return to sports; return to play; soccer